Pendampingan Pemberdayaan Ekonomi Ibu Rumah Tangga Desa Sampora Melalui Pendirian Warung Makan - Yanto, Yanto (Jurnal Pengabdian Masyarakat Charitas, 2021)
The community service aimed to a group of housewives in the Sampora village empower their household economy through the establishment of food stalls. The housewives who participated in this study were those who have been affected by the Covid-19 pandemic. They had been involved in previous community service activities which were organized by Faculty of Engineering, Atma Jaya Catholic University so that they already had the ability to process catfish into various types of food. The stage to establish the selling stalls used the PDCA method including the plan, do, check and action. This activity hopefully increase the household income for them